Pengaruh Kegel Exercise Terhadap Inkontinensia Urine Pada Lansia - Daryaman, Usan (stikes dharma husada bandung, 2021)
Elderly is someone who has entered the age of 60 years and over. In a group categorized as elderly, a process called the Aging Process will occur. One of the physical changes that occur in the elderly is in the urinary system, namely a decrease in the tone of the vaginal muscles and urinary tract muscles. This literature review aims to determine the effect of keggel exercise on urinary incontinence in the elderly. The method is descriptive analysis with data analysis method using Literature review. With the key words the effect of Kegel exercise, urinary incontinence in the elderly, the effectiveness of Kegel exercise, the effectiveness of pelvic floor exercise. The results of a literature review of 20 journals showed that only one journal presented that Kegel exercise did not have a significant change in the elderly with urinary incontinence. Meanwhile, 19 other journals said the opposite. This keggel exercise has been shown to strengthen the pelvic or pelvic muscles so that it can train and strengthen the external sphincter in the bladder. The conclusion is that there is an effect of urinary incontinence before and after the keggel exercise in the elderly. Keggel exercises can reduce urinary incontinence. Suggestions for future researchers are expected to be able to use a different research design to compare research subjects on the variable kggel exercise to urinary incontinence in the elderly.